2022
DOI: 10.1007/s10198-022-01531-0
|View full text |Cite
|
Sign up to set email alerts
|

Can drones save lives and money? An economic evaluation of airborne delivery of automated external defibrillators

Abstract: Background Out-of-hospital cardiac arrest is one of the most frequent causes of death in Europe. Emergency medical services often struggle to reach the patient in time, particularly in rural areas. To improve outcome, early defibrillation is required which significantly increases neurologically intact survival. Consequently, many countries place Automated External Defibrillators (AED) in accessible public locations. However, these stationary devices are frequently not available out of hours or to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 24 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…• Computer/prediction models: 17 studies used different strategies to localize optimal sites for placement of AED-drone bases and to estimate time gain compared with EMS response time. 35,[78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93] The data used varied according to geographic areas, quality and accessibility of historical OHCA data, drone type and input of diverse drone-flight details, existing EMS system, and volunteer responder programs. • Test flights/simulation studies and qualitative analysis: 9 studies of various aims, geography, and testing areas.…”
Section: Summary Of Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…• Computer/prediction models: 17 studies used different strategies to localize optimal sites for placement of AED-drone bases and to estimate time gain compared with EMS response time. 35,[78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93] The data used varied according to geographic areas, quality and accessibility of historical OHCA data, drone type and input of diverse drone-flight details, existing EMS system, and volunteer responder programs. • Test flights/simulation studies and qualitative analysis: 9 studies of various aims, geography, and testing areas.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…101 Five cost-effectiveness studies predicted the cost-effectiveness of a drone AED system to supplement existing systems to secure early defibrillation. 78,79,86,89,91 Task Force Insights A limited evidence base was identified, with most studies focused on theoretical drone base placement and estimated AED drone delivery times compared with standard EMS times. In contrast, only 1 pilot study and 1 case study reported the drone delivery of AEDs to real-world OHCAs.…”
Section: Summary Of Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…The integration of AI-driven solutions in the form of wearable devices, for instance, could provide real-time feedback to bystanders performing CPR, or even alert nearby medical professionals or trained individuals to rush to the scene [32]. This convergence of technology and medical intervention could redefine the OHCA landscape in the coming years [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…This results in an incremental cost-effectiveness ratio (ICER) of 23 568 euros [34]. Another study from Ro ¨per et al found that equipping drones with AEDs was a more cost-effective solution compared to the conventional strategy with stationary AEDs [35]. As there is a lack of clinical data on clinical outcomes these analyses are built on somewhat heavy assumptions.…”
Section: Dronesmentioning
confidence: 99%